T Cell Response in Patients with Implanted Biological and Mechanical Prosthetic Heart Valves - L. Barbarash; I. Kudryavtsev; N. Rutkovskaya; A. Golovkin (Hindawi Limited, 2016)
The study was aimed at assessing T cell subsets of peripheral blood from recipients of long-term functioning (more than 60 months) biological and mechanical heart valve prostheses. The absolute and relative number of CD4 and CD8 T cell subsets was analyzed: naïve (N, CD45RA+CD62L+), central memory (CM, CD45RA−CD62L+), effector memory (EM, CD45RA−CD62L−), and terminally differentiated CD45RA-positive effector memory (TEMRA, CD45RA+CD62L−) in 25 persons with biological and 7 with mechanical prosthesis compared with 48 apparently healthy volunteers. The relative and absolute number of central memory and naïve CD3+CD8+ in patients with biological prosthesis was decreased (p<0.001). Meanwhile the number of CD45RA+CD62L−CD3+CD8+ and CD3+CD4+ was increased (p<0.001). Patients with mechanical prosthesis had increased absolute and relative number of CD45RA+CD62L−CD3+CD8+ cells (p=0.006). Also the relative number of CD3+CD4+ cells was reduced (p=0.04). We assume that altered composition of T cell subsets points at development of xenograft rejection reaction against both mechanical and biological heart valve prostheses.